Meningkatkan Motivasi Kewirausahaan pada Masyarakat Desa Simpang Pelabuhan dalam Kecamatan Pemulutan - Fitri Anggraini; Fitriasuri Fitriasuri; Bakti Setyadi; Septiani Fransisca; Poppy Indriani; Efan Elpanso; Andrian Noviardy; Dina Mellita (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2026)
Community entrepreneurial motivation in Simpang Pelabuhan Dalam Village, Pemulutan District, remains relatively low, limiting local economic development. This condition is influenced by limited entrepreneurial knowledge, low self-confidence, and the perception that starting a business requires substantial capital. This community service program aimed to enhance entrepreneurial motivation through entrepreneurship socialization and training using a participatory approach. Community members were actively involved in problem identification, planning, implementation, and evaluation. The program included field observations, coordination with the village government, preparation of training materials, entrepreneurship workshops, interactive discussions, and evaluations conducted through interviews and questionnaires. The primary participants were members of the Karang Taruna and local residents. The results indicated that participants responded positively to the program and found the materials relevant and beneficial. Most participants reported increased interest, motivation, and confidence in starting independent businesses. They also gained a better understanding of entrepreneurship as a means of improving household welfare and recognized business opportunities based on the village’s local potential. Overall, the program effectively strengthened entrepreneurial motivation and contributed to community-based economic empowerment in Simpang Pelabuhan Dalam Village.